Analisis Capaian Sistem Penyedian Air Minum Perdesaan di Desa Sumberkima, Bali - Sudarsana, D.K. (Media Teknik Sipil, 2016)
The government announced a settlement infrastructure performance achievement in 2019 with 100% access to drinking water, 0% slump, 100% sanitary, known as 100-0-100 initiative. MDG'S 2015 settlement infrastructure sectors targeted are 68-10-62. To determine the achievement of this target needs to be evaluated. In this paper specifically analyze the achievement of rural drinking water supply system (SPAMDes). Descriptive method is used in this study. Studies conducted in the village Sumberkima, District Grokgak, Bali Province. Data collected by census method. Variables to determine the indicators of access to drinking water using the terms of reference of the Ministry of Public Works. The analysis finds access of drinking water service until August 2015 reached 85%. The achievement of the access to drinking water service is sourced from the piping connection from BUMDES 32%, 26% of shallow wells and deep wells 27%. Although the service is access to drinking water reached above the 2015 target (85%> 68%), but needs to be improved serviceability with access to drinking water piping connection system of BUMDES to improve the safer of quality.